Providing rehabilitation to patients recovering from COVID‐19: A scoping review. Issue 2 (7th October 2021) - Wasilewski, Marina B.; Cimino, Stephanie R.; Kokorelias, Kristina M.; Simpson, Robert; Hitzig, Sander L.; Robinson, Lawrence
Abstract: Objective: To synthesize the nature and extent of research on rehabilitation care provision to patients with COVID‐19. Specifically, we aimed to (1) describe the impact of COVID on patients and associated rehabilitation needs, (2) outline the adaptations and preparations required to enable the provision of COVID rehabilitation, (3) describe the types of rehabilitation services and treatments provided to COVID patients, and (4) identify barriers and facilitators to delivering COVID rehabilitation. Literature Survey: We searched Medline, PsychINFO, Embase, and CINAHL on June 26, 2020 using key words such as "rehabilitation, " "physical medicine, " "allied health professionals, " and variations of "COVID." The search was updated on October 13, 2020. We included articles published in English and that focused on some aspect of COVID rehabilitation for adults. We excluded articles focused on pediatric populations and those not focused (or minimally focused) on rehabilitation for COVID patients. Methodology: Data were charted based on article type (ie, primary data, secondary data, guidelines). Key information extracted included (1) COVID sequelae; (2) rehabilitation adaptations; (3) structure, function, and content of rehabilitation services/programs; (4) facilitators and/or barriers to providing COVID rehabilitation; and (5) recommendations for COVID rehabilitation programming. Data were synthesized narratively. Synthesis: In total, 128 articles were included in the review that reported primary data (n = 33), secondary data (n = 82), and clinical practice/patient self‐management guidelines (n = 13). Evidence begins to suggest that rehabilitation is necessary and valuable for addressing COVID‐related declines in health, function, and well‐being. Most articles recommended that an individualized rehabilitation program be provided across the continuum of care by an interdisciplinary team of professionals and that the nature and extent of rehabilitation be informed by the care setting and COVID severity. Most issues that challenged COVID rehabilitation delivery were directly addressed by the facilitators and adaptations identified. Conclusions: Future recommendations include a greater emphasis on the psychosocial aspects of COVID rehabilitation, inclusion of families in rehabilitation planning, and the use of qualitative approaches to complement clinical data.